Effect of Fermentation Time and Cassava Varieties on Water Content and the Yield of Starch from Modified Cassava Flour (MOCAF) - Nurud Diniyah; Achmad Subagio; Riri Nur Lutfian Sari; Pradiska Gita Vindy; Alif Ainur Rofiah (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
MOCAF (modified cassava flour) is a high potential food product. This product can be used to replace wheat flour in the manufacture of various food products. However, there is no characterization of starch properties of MOCAF. The efforts to improve the quality of starch from cassava starch by fermentation process using a combination of enzymes and microbes  from Lactic acid bacteria.The purpose of this research is to determine the influence of fermentation time to yield and moisture content. Single factor randomized block design with 3 (three) levels i.e fermentation time (0, 12, and 24 hours) with two group namely varieties of cassava Cimanggu and Kaspro. Cimanggu and Kaspro cassava varieties were used to compare the properties of starch due to different fermentation time (0, 12 and 24 hours) with triplicate. The results showed the yield and moisture content were affected by fermentation time. Average moisture content ranged from 13.3 to 13.8% with the starch yield is 38-59%. Application of starch MOCAF can be used for food, cosmetics, and medicines industry.Keywords : modified starch, cassava, fermentation, yield